Mapping General Anesthetic Sites in Heteromeric γ-Aminobutyric Acid Type A Receptors Reveals a Potential For Targeting Receptor Subtypes. (November 2016) - Forman, Stuart A.; Miller, Keith W.
Abstract : IV general anesthetics, including propofol, etomidate, alphaxalone, and barbiturates, produce important actions by enhancing γ-aminobutyric acid type A (GABAA ) receptor activation. In this article, we review scientific studies that have located and mapped IV anesthetic sites using photoaffinity labeling and substituted cysteine modification protection. These anesthetics bind in transmembrane pockets between subunits of typical synaptic GABAA receptors, and drugs that display stereoselectivity also show remarkably selective interactions with distinct interfacial sites. These results suggest strategies for developing new drugs that selectively modulate distinct GABAA receptor subtypes. Abstract : Published ahead of print May 10, 2016.